EXPLORING THE LINK BETWEEN CHRONIC OBSTRUCTIVE PULMONARY DISEASE, BRONCHIAL ASTHMA, AND LIPID PROFILES: A CROSS-SECTIONAL STUDY. - Chatterjee, Shouvik; Thakur, Deepak Kumar; Kumar, Rahul; Choudhary, Binod Kumar (Student’s Journal of Health Research Africa, 2023)
Introduction: This pilot cross-sectional study intended to explore the relationship between Chronic Obstructive Pulmonary Disease (COPD), Bronchial Asthma, and serum lipid levels (HDL, LDL, Total Cholesterol, Triglycerides) as well as serum urea and creatinine. Conducted at Patna Medical College and Hospital, Patna it involved 21 clinically diagnosed stable COPD and bronchial asthma patients. The study cohort was categorized into Mild, Moderate, and Severe COPD based on GOLD criteria. Methods: Data collection involved detailed medical histories and fasting blood specimens. Serum lipids were assessed via enzymatic colorimetric assays, and LDL, HDL, and total cholesterol levels were calculated. Fasting and postprandial blood sugar levels were measured. Results: The study revealed associations between COPD severity and lipid profiles. Notably, Total Cholesterol was 177.19 mg/dL, HDL was 41.87 mg/dL, LDL was 109.92 mg/dL, and Triglycerides were 115.58 mg/dL. An increase in airway resistance, detectable with an impulse oscillometer, was observed even with minor airway alterations. The study indicated significant correlations between serum triglycerides, LDL, LDL/HDL ratio, cholesterol/HDL ratio, and elevated airway resistance in individuals with bronchial asthma and COPD. Conclusion: This pilot study provides initial insights into the interplay between COPD, Bronchial Asthma, and lipid profiles. While lipid findings generally fell within the normal range, elevated LDL levels emphasize the need for monitoring and potential interventions to mitigate cardiovascular risk in COPD patients. Recommendations: Healthcare providers should regularly monitor serum lipid levels, urea, and creatinine in COPD and bronchial asthma patients, particularly those with severe COPD, to detect and manage abnormalities early, potentially enhancing patient outcomes. Further research with larger sample sizes is required to validate these findings and develop comprehensive guidelines for the care of COPD and bronchial asthma patients.